Implementasi Algoritma AHP Dalam Penentuan Penerima Bantuan Jamban di Desa Titidu Kwandang - Suhardi Rustam; Sumarni sumarni (Universitas Asahan, 2023)
The provision of latrine assistance addresses problems to the community and is at the same time one of the important efforts in improving sanitation and Public Health. The Titidu village government has provided toilet assistance to underprivileged communities since 2015 with a total of 25 RTM. From the results of data collection in Titidu Village, the following data are presented on the recipients of Titidu Village latrines for the last three years 2017 to 2019.in the process of determining the acceptance of latrine assistance still makes it difficult for the Titidu village government which allows problems to occur in data processing, namely determining that people cannot afford to receive latrine assistance amid the large number of data on the underprivileged population in Titidu Village. In this study will design a Decision Support System for latrine recipients using the AHP method and as a Decision Support System to determine the recipient of latrine assistance, that the system for determining the recipient of latrine assistance will be used by the Admin, village government and Village Head. The Admin is titidu village staff in charge of inputting criteria data and the assessment selection process, the admin can also access the data of latrine recipients and get the selection results. The user of the Pemdes system is the head of the Government section in charge of inputting data on latrine recipients, and the other system user is the head of Titidu village who will receive the results of the selection of latrine aid recipients. the results of this study are by using 60 data and experimental results of recipients with ranked weighting, 5 people who deserve to be given toilet assistance according to the highest to lowest weighting results, namely Djafar Polamolo, Suleman Amir, Azis Laiya, Wani Paliki and Yunus Ibrahim. And also have obtained the performance and effectiveness of Decision Support Systems latrine beneficiaries using the method Analitycal Hierachy Process (AHP).